Odpowiedzi

Najlepsza Odpowiedź!
2009-11-25T15:24:22+01:00
A) (a-4)(a+5)=a²+5a-4a-20=a²+a-20
b)(7b+3)(2-4b)= 14b-28b²+6-12b= -28b²-2b+6
c)(-3c+2d)(2c-6)=-6c²+18c+4cd-12d
d)(9s-2t)(7t-s)= 63st-9s²-14t+2st=65st-9s²-14t
e)(-10m+3n)(5n-4)=-50mn+40m+3n²-12n
f)(3kl+8k)(4-2l)=12kl-6kl²+32k-16kl=-4kl-6kl²+32k
g)(4xy+3x)(2y+5x²y)=8xy²+20x³y³+6xy+15x³y
h)(-2p²q-3p)(5pq-3p²q²) =-10p³q²+6pdo4q³-15p²q+9p³q²

dobrze jest rozwiazane:-)
2009-11-25T15:31:32+01:00
A) (a-4)(a+5)=
a²+5a-4a-20=
a²+a-20

b)(7b+3)(2-4b)=
14b-28b²+6-12b=
-28b²+2b+6

c)(-3c+2d)(2c-6)=
-6c²+18c+4cd-12d

d)(9s-2t)(7t-s)=
63st-9s²-14t²+2st=
65st-9s²-14t²

e)(-10m+3n)(5n-4)=
-50mn+40m+15n²-12n

f)(3kl+8k)(4-2l)=
12kl-6kl²+32k-16kl=
-4kl-6kl²+32k

g)(4xy+3x)(2y+5x²y)=
8xy²+20x³y³+6xy+15x³y

h)(-2p²q-3p)(5pq-3p²q²)=
-10p³q²+6p⁴q³-15p²q+9p³q²
2009-11-25T16:14:14+01:00
A)a²+5a-4a-20=
a²+a-20

b)14b-28b²+6-12b=
-28b²+2b+6

c)-6c²+18c+4cd-12d

d)63st-9s²-14t²+2st=
65st-9s²-14t²

Nie całość, tylko część przykładów(znaczna).
Ale mam nadzieje ,że pomogłam :)) !